MO1059: A Case Series of 2 Patients with Perdialytic Dialysis Headache: Is There a Role for Isonatremic Dialysis?. (3rd May 2022) - Ossmane, Rime; Antonio Urena Torres, Pablo; Attaf, David; Rousseau, Philippe
Abstract: BACKGROUND AND AIMS: Per-dialytic headache (PDH) is a frequent complication of hemodialysis (HD) and often a challenge for nephrologists. Its pathophysiology has been though to involve sodium and/or osmotic variation during HD session. We assess here the effect of an Automatic Individualized Sodium Module Management (Na Mngt module) embedded into the dialysis machine on the PHD of two patients. Na Mngt module assesses pre-dialytic plasma sodium concentration and measures it through all the HD duration. Na Mngt module automatically controls the sodium concentration of the dialysate fluid and limits the diffusive sodium load during the HD session. METHOD: 2 women aged of 87 and 76 years consistently reported unbearable PDH and nausea during several Online-Hemodiafiltration (HDF) sessions. They did not present other possible causes of PHD, including migraine, nervous depression, disequilibrium syndrome, and arterial hypertension. We suspected that the PDH was favored by dialysis-induced high plasma osmolarity (conductivity) in both patients (conductivity: 135–140 and 138 mmol/L) and decided to put them on Na Mngt module to align the sodium concentration of the dialysate fluid with their predialytic plasma sodium concentration. RESULTS: After Na Mngt's activation, The PDH observed in both patients disappeared almost instantly. For both patients '1' and '2', the evolution of the main dialysis parameters before and after Na Mngt activation where respectively: Dry Weight (patient1: 42/41 Kg; patient2: 61/60.5 Kg); Pre-dialysis Sodium (patient1: 131/133 mmol/L; patient2: 143/138 mmol/L); Conductivity (patient1: 135–140/136+/-4 mmol/l; patient2: 140/139 mmol/L); IDWG (patient1: 2.5/2, patient2: 2/1.8 Kg); UF (patient1: 2/1.5 L/session; patient2: 2/1.6 L/session); Diffusive sodium balance (patient1: 10/2 g/session; patient2: 8/0 g/session). The Fig. 1 depicts the evolution of pre- and post-dialysis plasma sodium concentration before and after Na Mngt module activation for patient 1. The Fig. 2 shows for patient 2 the conductivity of the dialysate (in blue) throughout the session compared to the plasma conductivity (in red) with activation of Na Mngt module: the diffusive Na transfer remained around 0 g during ALL the session. For Patient 2, the predialytic plasma Na + was 139 mmol/L, and total Na removed was 18.8 g for the entire session. To obtain these results the dialysis machine module adjusted the dialysate Na within the range of 140–144 mmol/L. CONCLUSION: This case report suggests that the Na Mngt module controls the diffusive sodium transfer during HD, reduces sodium load, osmotic fluctuations, and prevents PHD. Na Mngt activation allows isonatremic prescription of sodium with less variation between pre- and post- dialysis plasma sodium concentrations and decreases diffusive Na when isonatremic mode is selected. 'Patient 2' shows (Fig. 2 ) that the Na Mngt tool set a dialysate conductivity slightly higher than Na plasma to obtain an iso-natremic profile. Further controlled clinical study are needed to confirm the effect of the Na Mngt tool on intradialytic (PDH, hypotension) and interdialytic (thirst, IDWG) symptoms.